FORECASTING OF PALM OIL FRUIT FRESH BUNCHES (FFB) PRICES IN NATIONAL AND BENGKULU PROVINCE: ARIMA MODEL APPLICATION - Yulia Herdiyanti; Ketut Sukiyono (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
CPO price fluctuations that occur also have an impact on the price of palm oil FFB at the National and Bengkulu Province. Because, palm oil is the raw material for making CPO. This study aims to determine the best ARIMA model for predicting the price of palm oil FFB at the National and Bengkulu Province, as well as to find out the results of forecasting palm oil prices at the National and Bengkulu Province in 2021. This study uses secondary data, namely monthly data from palm oil producer price data national and Bengkulu Province in 2011-2020. The model used for this research is ARIMA. The results of the study show that models are suitable for forecasting at the National and Bengkulu Province, namely ARIMA (2,1,8) and ARIMA (2,1,7). The results of forecasting the highest national oil palm FFB price occurred inin January 2021 of Rp. 118,075/100 kg and the lowest national palm oil FFB price occurred in December 2021 of Rp. 115,696/100 kg. while the results of forecasting the highest price of oil palm FFB in Bengkulu Province occurred in December 2021 amounting to Rp.148,653/100 kg and the lowest price of oil palm FFB in Bengkulu Province occurred in January 2021 amounting to Rp.144,798/100 kg.